Assessment of ceftolozane/tazobactam stability in elastomeric devices and suitability for continuous infusion via outpatient parenteral antimicrobial therapy. Issue 3 (27th September 2021) - Jamieson, Conor; Drummond, Felicity; Hills, Tim; Ozolina, Laima; Gilchrist, Mark; Seaton, R Andrew; Santillo, Mark; Wilkinson, Alan-Shaun; Allwood, Michael C
Abstract: Objectives: To investigate the stability of ceftolozane/tazobactam 5 mg/mL and 20 mg/mL solutions for infusion in two elastomeric devices: FOLFusor LV10 (Baxter Healthcare) and Easypump ® II (B. Braun Medical Ltd) and determine if an extended shelf life of up to 8 days storage at 2–8°C plus 24 h 'in use' at 32°C was achievable. Methods: Testing was as per the latest NHS Pharmaceutical Quality Assurance Committee Yellow Cover Document (YCD) requirements. A stability-indicating LC method was used for assessing the stability of solutions of ceftolozane/tazobactam at 5 mg/mL and 20 mg/mL (combined concentration of both actives) respectively, tested in two batches in triplicate ( n =  3) at five timepoints according to the requirements of the YCD. Results: Ceftolozane/tazobactam, diluted in 0.9% w/v sodium chloride at 5 mg/mL and 20 mg/mL, degraded during in-use storage at 32°C with <95% remaining after 18 h for some device/concentration combinations and all device/concentration combinations at 24 h, respectively. The data does support extended storage of up to 8 days at 2–8°C plus 12 h at 32°C 'in-use' when using either FOLFusor LV10 or Easypump ® II devices and is compliant with YCD. Conclusions: Solutions of ceftolozane/tazobactam can be administered in outpatient parenteral antimicrobial therapy (OPAT) services following refrigerated storage for up to 8 days, when limited to a 12 h infusion at in-use temperature of 32°C. For UK OPAT services where twice daily dosing is feasible, our data provides another treatment option for challenging infections. In countries where a 10% loss of ceftolozane/tazobactam is acceptable, a 24 h infusion is supported by the data.